Tonal and "Anti-Tonal" Cognitive Structure in Viennese Twelve-Tone Rows - von Hippel, Paul T.; Huron, David (Empirical Musicology Review, 2020)
We show that the twelve-tone rows of Arnold Schoenberg and Anton Webern are "anti-tonal"—that is, structured to avoid or undermine listener's tonal schemata. Compared to randomly generated rows, segments from Schoenberg's and Webern's rows have significantly lower fit to major and minor key profiles. The anti-tonal structure of Schoenberg's and Webern's rows is still evident when we statistically controlled for their preference for other row features such as mirror symmetry, derived and hexachordal structures, and preferences for certain intervals and trichords. The twelve-tone composer Alban Berg, by contrast, often wrote rows with segments that fit major or minor keys quite well.